Persepsi Publik Kota Denpasar Terhadap Konstruksi Media Sosial X Dalam Pemberitaan Isu Permasalahan Sampah - I Nyoman Satrya Sanjaya; I gusti Agung Ananda Putra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The waste problem in Denpasar City has evolved into an ecological crisis that triggers public discourse in the digital realm, particularly through the X social media platform (formerly Twitter). This study aims to understand and analyze how the public perception of Denpasar City is formed towards the construction of X social media in reporting the issue of waste problems. This research uses a descriptive qualitative approach with the analytical framework of the Stimulus-Organism-Response (S-O-R) Theory. Data collection was carried out through in-depth interviews with 11 informants (consisting of community representatives, policymakers, communication experts, and social media managers) determined by purposive sampling techniques, supported by netnographic observation and documentation studies. The results showed that the stimulus (S) constructed on X was visual-realistic and narratively sarcastic, dominated by citizen journalism complaints rather than official government releases. At the organism stage (O), the public internalized the stimulus with full attention due to empirical proximity (actual odor and traffic congestion in the field). This culminates in a response (R) in the form of public perception formation divided into three dimensions: cognitively, the public evaluates the government system as being in a state of emergency failure; affectively, there is polarization between anger towards the bureaucracy and empathy for field workers; and conatively, it triggers cyber advocacy (digital criticism) as well as the adoption of independent waste management. X social media has proven to transform into a catalyst for the ecological disappointment of the Denpasar City community.